Predicting Growth Rate of Students’ Achievement in Mathematics Using Mathematical Growth Model - Obasi, Chinedu; Ugo, Chima (SJME (Supremum Journal of Mathematics Education), 2018)
Students’ mathematics achievements in secondary school have an influential effect on their performance in university and their future careers. There are numerous innovative teaching strategies which are promising and have shown to improve students’ achievement in mathematics; one will wonder if there will be corresponding achievement growth in mathematics. Therefore, this paper predicts growth rate of students’ achievement in mathematics using mathematical growth model. A developmental survey design was employed where students’ WAEC mathematics achievement results from 1991-2016 were collected from the Development Division, West African Examination Council (WAEC) Lagos, Nigeria. The Logistic growth mathematical model was used to compute predicted achievement growth rate. The Statistical Package for Social Sciences (SPSS) was also used to plot the graph of the achievement data from 1991 to 2016. The result indicates that the predicted growth rate of students’ achievement in mathematics is approximately increased by 25.3% per year. This shows a weak upward trend in predicted rate of achievement at credit level and consequently indicates unsteady sustainability in mathematics achievement as well as economic growth. It is recommended among others that there should be investigation into factors responsible for the weak and unsteady achievement growth in WAEC general mathematics in Nigeria. Also, effective teaching and learning of mathematics at all levels of schooling should be ensured by all concerned in other to sustain the achievement growth in the subject.